Technological leadership and firm performance in Russian industries during crisis; Journal of Business Venturing Insights; Vol. 15 - Anokhin S. A. Sergey Aleksandrovich; Spitsin V. V. Vladislav Vladimirovich; Akerman E. N. Elena Nikolaevna; Morgan T. Todd (2021, 2021)
Title screen